A correlation studies of Indoor Environmental Quality(IEQ) towards productive workplace - Mahbob, N.S.; Kamaruzzaman, S.N.; Salleh, N.; Sulaiman, R. (2011)
Productivity is one of the major contributions to build the economic growth in every country. Human performance and working environment is related to each other and have a major impact on the work efficiency and production output. Nowadays, most of the offices are fully equipped with mechanical ventilation and fully air-conditioned. Office building occupants spend almost 12 hours daily indoor and that makes good indoor environment very important due to achieve workers satisfaction and more comfortable. The objective of this paper is to observe the correlation of IEQ and productivity in working place. It is believed that this study have been able to provide a better understanding. It is hoped that this useful findings would serve as a reference in the future to the building industry, academicians and also public in sustaining better indoor environmental quality.